The synthesis of phosphate and vanadate apatites using an aqueous one-step method. (8th May 2017) - Yoder, Claude H.; Havlusch, Maxwell D.; Dudrick, Robyn N.; Schermerhorn, Janse T.; Tran, Linh K.; Deymier, Alix C.
Graphical abstract: The one-step aqueous method for apatite synthesis does not require addition of reagents and no adjustment of solution pH. It requires less equipment and less time and produces smaller crystallites than the traditional aqueous addition method. Abstract: A modification of the aqueous addition method for the synthesis of apatites is described. This one-step method does not require addition of reagents and no adjustment of solution pH and therefore requires less equipment and less time than the traditional aqueous addition method. It can be used with a variety of starting materials to produce both phosphate and vanadate apatites with good purity and yield. The method generally produces smaller crystallites with average size in the 30–50 nm range. The effects of synthesis variables such as the nature of the reactants, control of pH, and digestion temperature and time are discussed.